Regulon engineering as a rapid, rational approach for non-native substrate catabolism in Saccharomyces cerevisiae - Sullivan, Sean. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Nikhil Nair.; Committee: Kyongbum Lee, Joshua Kritzer, and Ahmad Khalil.; Keywords: Bioengineering, and Microbiology.